2016
DOI: 10.1371/journal.pone.0161792
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Resveratrol Supplementation against Non-Alcoholic Fatty Liver Disease: A Meta-Analysis of Placebo-Controlled Clinical Trials

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease with rising prevalence. Increasing evidence has demonstrated that resveratrol, a dietary phytochemical, is capable of attenuating NAFLD development and progression; however, results from clinical studies are inconsistent and inconclusive. Here, we conducted a meta-analysis to evaluate the efficacy of resveratrol on NAFLD, using several parameters to provide new insights for clinical application. We systematically searched EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 34 publications
(51 reference statements)
3
31
1
Order By: Relevance
“…Until now, there has been a lack of proven medical therapies for NAFLD treatment (Popov & Lim, 2015). As knowledge about the mechanisms of NAFLD pathogenesis is growing, researchers are aiming to find effective therapeutic agents across pharmacology, nutrition, and complementary fields (Kanai et al, 2016;Trovato, Catalano, Martines, Pace, & Trovato, 2015;Zhang et al, 2016). Although the evidences showed that herbal remedies are generally better tolerated than synthetic medications (Izzo, Hoon-Kim, Radhakrishnan, & Williamson, 2016), there is a lack of conclusive information in efficacy and their possible side effect on diseases, and this issue made it one of the important problems faced by doctors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there has been a lack of proven medical therapies for NAFLD treatment (Popov & Lim, 2015). As knowledge about the mechanisms of NAFLD pathogenesis is growing, researchers are aiming to find effective therapeutic agents across pharmacology, nutrition, and complementary fields (Kanai et al, 2016;Trovato, Catalano, Martines, Pace, & Trovato, 2015;Zhang et al, 2016). Although the evidences showed that herbal remedies are generally better tolerated than synthetic medications (Izzo, Hoon-Kim, Radhakrishnan, & Williamson, 2016), there is a lack of conclusive information in efficacy and their possible side effect on diseases, and this issue made it one of the important problems faced by doctors .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the adoption of proper interventions to control NAFLD is important for any healthcare system. In modern medicine, lifestyle modification, in the form of diet, physical exercise, and weight loss, is considered as the best solution for NAFLD management, but these changes are difficult for many people, so an effective adjunctive therapy with minimal side effects is needed (Hekmatdoost et al, ; Zhang et al, ). Recent evidence suggests that plant‐derived natural products such as flavonoids and polyphenols, which are predominantly found in fruits, vegetables, and tea, may be promising in NAFLD management by reducing liver enzymes and acting as antioxidant and antiinflammatory agents (Marventano et al, ; Van De Wier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, a subtle potential of resveratrol against NAFLD has been demonstrated only by two clinical trials. 133,134 It is suggested that the frequent coexistence of other pathological conditions in NAFLD patients may SINGH ET AL.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The mechanisms through which resveratrol alleviates fibrosis are shown in Figure 4. Although resveratrol has been shown to have beneficial biological functions in the antifibrotic response, its efficacy in NAFLD is insignificant; indeed, a meta-analysis conducted by Zhang et al[110] indicated that resveratrol can only improve LDL and total cholesterol levels in patients with NAFLD.…”
Section: Novel Therapeutic Targets In Liver Fibrosismentioning
confidence: 99%